Pemilihan Krim Imiquimod 5% Sebagai Terapi Kombinasi Enukleasi Pada Genital Molluscum Contagiosum Ko-Infeksi HIV - Rhea Tiara Dinata (Faculty of Medicine and Health Sciences, UIN Maulana Malik Ibrahim Malang, 2025)
A b s t r a c t Keyword : Immiquimod,Genital Molluscum Contagiosum, HIV,Enucleation,Combination Therapy Introduction: Molluscum contagiosum (MC) is clinically characterized by dome-shaped, white to skin-colored papules that are typically self-limiting. In immunocompromised individuals, MC lesions tend to delayed clinical resolution. Aims: This case report presents a case of genital MC treated with combination of immiquimod cream 5% with enucleation. Case: A 27-year-old female presented with skin-colored papules in the genital area, accompanied by mild pruritus (VAS 3/10 that has been diagnosed with HIV nine months prior and was adherent to antiretroviral therapy. Physical examination revealed dome-shaped nodules with central umbilication, varying in size and shape. Dermoscopic examination showed central pink-white polylobular amorphous structures surrounded by crown vessels. Absolute CD4 count of 194 cells/μL with non-reactive VDRL and TPHA. Histopathological examination of the nodule revealed foci of epithelium containing intracytoplasmic eosinophilic inclusion bodies (Henderson-Patterson bodies). The patient was diagnosed with genital MC and was treated with 5% imiquimod cream for 12 weeks, then enucleation was performed for persistent lesions. Discussion: In immunocompromised individuals, MC lesions tend to delayed clinical resolution. Immiquimod cr 5% for 12 weeks showed partial clinical cleareance. Enucleation that performed for persistent lesion with total clearance without any recurrence.Conclusion: Combination of Imiquimod 5% cream as immunomodulator with enucleation can be considered a therapeutic option for genital molluscum contagiosum in immunocompromised individuals. Kata kunci : Immiquimod, Molluscum Contagiosum GenitalHIV,Enukleasi,Terapi kombinasi A B S T R A KPendahuluan: Moluskum kontagiosum (MK) secara klinis ditandai dengan papul, berbentuk kubah, sewarna kulit hingga berwarna putih yang dapat sembuh dengan sendirinya. Pada imunocompromised perbaikan klinis dapat lebih lama. Tujuan: Laporan kasus ini memaparkan sebuah kasus MK genitalis ko-infeksi HIV yang diberikan terapi kombinasi krim immiquimod 5% dan enukleasi. Kasus: Perempuan, 27 tahun dengan keluhan muncul benjolan sewarna kulit pada area kelamin yang disertai dengan rasa gatal VAS 3/10, telah terdiagnosis HIV sejak 9 bulan sebelumnya dan rutin mengkonsumsi ARV. Pemeriksaan fisik didapatkan lesi nodul berbentuk kubah dengan umbilikalis sentral, bentuk dan ukuran bervariasi. Pemeriksan dermoskopi menunjukkan struktur amorf, polilobular, putih kemerahan di tengah dengan crown of vessels. Jumlah CD4 absolut 194 sel/Μl, tes serologis VDRL dan TPHA non-reaktif. Pemeriksaan histopatologi pada nodul ditemukan intracytoplasmic eosinophilic inclusion bodies (Handerson- Patterson Bodies). Pasien didiagnosis MK genital dan diberikan terapi krim immuquimod 5% selama 12 minggu yang dilanjutkan dengan enukleasi pada beberapa benjolan yang masih menetap. Diskusi: Pada individu dengan immunocompromised, lesi MK dapat muncul dengan ukuran lebih besar dengan perbaikan klinis lebih lama. Krim immiquimod 5% selama 12 minggu memberikan perbaikan klinis namun tidak cukup signifikan. Beberapa lesi yang menetap dilakukan enukleasi dengan perbaikan klinis tanpa terjadinya kekambuhan. Kesimpulan: Kombinasi terapi krim imiquimod 5% dengan enukleasi dapat digunakan sebagai pilihan terapi MK genitalis pada kondisi immunocompromised.